Evaluation of Serologic Markers for Transfusion Transmitted Infectious Diseases For Allogeneic Blood Donors in Puerto Rico - Martínez-Díaz, Hildabelís; Frye-Maldonado, Aislinn C.; Climent-Perís, Consuelo; Vélez-Rosario, Román (Puerto Rico Health Sciences Journal, 2019)
see manuscript